Logotherapy for couples: An anthropological, methodological and attitudinal proposal - Salomón, Alejandro Khaled (2019)
In this article, we provide a perspective on couple psychotherapy from a humanistic - existential - phenomenological orientation, specifically from the perspective of logotherapy and the thinking of Viktor Frankl. This represents an attempt to understand the human being as a being that is a relationship, and in the possibility of making a truly encounter with another, based on an existential attitude of openness and authenticity, which mean, to be willing to the world, to You who presents as kind person, appropriatingthe risk of being genuine and letting himself be touched by all the valuable things that can be found and  realized in the bond, which is what happens between a Self and a You. Communication is understood asthe foundation of the relationship, constituting a key piece of work to understand the dynamics of the couple. Likewise, a libertarian view of human relations is developed, which emphasizes individuality andresponsibility as the basis for forming a community as a couple, and with an axiological vision of the relationship that contemplates values that, when experienced, can contribute to life having more senseIn the same way, a therapeutic proposal sustained in phenomenology is developed as a methodology andattitude towards the couple, a Socratic dialogue between three, which seeks the unfolding of the spiritualin the couple in terms of self-distance and self-transcendence, in order to be more aware of the way theyrelate and assume the risk of deciding for some possibility, perhaps to go out to meet the other and live amore satisfying relationship.